Perlindungan Hak Cipta di Bidang Desain Grafis Dalam Penjualan Jasa Desain di Media Sosial - Ahya Mofidi Lahida; Adi Sulistiyono (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to identify and analyze how social media as a tool for selling graphic design services is then linked to the legal consequences for copyright objects as well as the legal protection given to copyright owners reviewed using Law Number 28 of 2014. This research is a research normative law with a statutory approach. The legal sources used consist of primary legal materials and secondary legal materials. The legal language analysis technique uses literature study, namely books, journals, articles related to the problem topic. The results of this research show that Law Number 28 of 2014 concerning Copyright has basically provided direct legal protection for graphic design creators for the graphic design work they upload to social media. In protecting their creations, graphic design creators can take legal action, both preventive and repressive.